Presence of alternative lengthening of telomeres mechanism in patients with glioblastoma identifies a less aggressive tumor type with longer survival - McDonald, Kerrie L.; McDonnell, Julie; Muntoni, Alessandra; Henson, Jeremy D.; Hegi, Monika E.; Deimling, Andreas von; Wheeler, Helen R.; Cook, Ray J.; Biggs, Michael T.; Little, Nicholas S.; Robinson, Bruce G.; Reddel, Roger R.; et al. (Journal of neuropathology and experimental neurology, 2010)
Patients with glioblastoma (GBM) have variable clinical courses, but the factors that underlie this heterogeneity are not understood. To determine whether the presence of the telomerase-independent alternative lengthening of telomeres (ALTs) mechanism is a significant prognostic factor for survival, we performed a retrospective analysis of 573 GBM patients. The presence of ALT was identified in paraffin sections using a combination of immunofluorescence for promyelocytic leukemia body and telomere fluorescence in situ hybridization. Alternative lengthening of telomere was present in 15% of the GBM patients. Patients with ALT had longer survival that was independent of age, surgery, and other treatments. Mutations in isocitrate dehydrogenase (IDH1mut) 1 frequently accompanied ALT, and in the presence of both molecular events, there was significantly longer overall survival. These data suggest that most ALT+ tumors may be less aggressive proneural GBMs, and the better prognosis may relate to the set of genetic changes associated with this tumor subtype. Despite improved overall survival of patients treated with the addition of chemotherapy to radiotherapy and surgery, ALT and chemotherapy independently provided a survival advantage, but these factors were not found to be additive. These results suggest a critical need for developing new therapies to target these specific GBM subtypes.
Gesehen am 12.04.2023